Respiratory Health Among School Children Around An Electronic Waste Site, Agbogbloshie, Compared With A Control Group, Madina Zongo - Okotah, G.E. (University of Ghana., 2019)
Background: Poor air quality bas been associated with adverse health effects among humans, and inhaled pollutants can directly impact on cardiovascular and respiratory health, resulting in increased morbidity and mortality. Informal electronic waste recycling is often not regulated and activities could result in direct pollution of ambient air and surrounding environment with toxic chemicals such as inorganic heavy metal dust, organic bound particulate matter, toxic smoke from open burning of electrical cables among others. Although several studies have been conducted among e-waste workers to assess the effect of e-waste exposure on health, not many studies have been conducted among children who are at risk of developing respiratory symptoms. Objective: To assess the respiratory health of children in schools around the informal e-waste site in Agbogbloshie (exposed site) and Madina (unexposed or control site) Methods: An analytical cross-sectional study was conducted from May 2019 - July 2019 among school children at Agbogbloshie and Madina. For respiratory health, a standardized questionnaire and an Easyone spirometer were used to assess self-reproted respiratory symptoms and lung function respectively. Also, an Aerocette 831 was used to assess air quality inside and outside various classrooms by measuring particulate matter (PM₁,₂₅. and PM₁₀) concentrations. Multi-stage sampling method was used to proportionally select study participants from each school. Mean values and standard deviations were computed for lung function indices; FEVl, FVC and FEVl/FVC and PM. Pearson correlation analysis was used to test for association between PM₂₅ S and lung function Indices. Results: The most common self-reported respiratory symptoms among school children at Agbogbloshie and Madina were; sneezing (24.8%vs I7.1%), rhinorrhea (17.8%.vrs 8.I%) and cough (20.2% vs 26.1%). The mean Lung function indices for Agbogbloshie and Madina were: FEVI (1.652±0.508 vs 1.677±0.696), FVC (2.2409±0.967 vs 2.745±1.904, p<0.05) and %FEVI/FVC (76.329±17. 705 vs 68. 74±21.13S. (p<0.05). The average PM₂₅ concentrations of indoor and outdoor air sampled on the first day of measurement were significantly higher in Agbogbloshie compared with Madina as compared to values on the second day of air sampling. Conclusion: The findings suggests that school children around Agbogbloshie recorded higher respiratory symptoms and reduced FVC compared with their counterparts in Madina. Keywords: Respiratory health. Electronic waste recycling. Lung function, Particulate Matter
MSc Occupational Hygiene Degree
Keywords: Respiratory health; Electronic waste recycling; Lung function; Particulate Matter